2006
DOI: 10.1677/joe.1.06709
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposure of adult male rats to dietary phytoestrogens reduces fecundity and alters epididymal steroid hormone receptor expression

Abstract: Phytoestrogens are plant-derived compounds with oestrogenic activity. They are common in both human and animal diets, particularly through soy-based foods. This study assessed whether exposure of adult male rats to a high phytoestrogen diet for 3-25 days affected their fertility, and assessed possible mechanisms through which phytoestrogens may disrupt fertility. Adult males, fed a high phytoestrogen diet for 3 days, demonstrated significantly reduced fecundity. This effect was transient, with fecundity return… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 46 publications
6
25
0
2
Order By: Relevance
“…In the same vein, decrease in sperm motility suggests alteration of sperm maturation in the epididymis. Also, the increase in the sperm head abnormality in caffeine treated-animals is indicative of induced mutation on the sperm cells during spermatogenesis as observed by Ekaluo et al (2009), Glover and Assinder (2006) and Ikpeme et al (2010).…”
Section: Discussionmentioning
confidence: 68%
“…In the same vein, decrease in sperm motility suggests alteration of sperm maturation in the epididymis. Also, the increase in the sperm head abnormality in caffeine treated-animals is indicative of induced mutation on the sperm cells during spermatogenesis as observed by Ekaluo et al (2009), Glover and Assinder (2006) and Ikpeme et al (2010).…”
Section: Discussionmentioning
confidence: 68%
“…The discrepancy in testosterone between this study and that of Weber et al may be due to the longer exposure period used there (35 vs 24 days). No changes in testosterone concentrations have been described in adult-only exposure studies for 3 days (Glover & Assinder 2006) or 14 days (Fritz et al 2002). Therefore, increased apoptosis of spermatocytes and round spermatids did not appear to be due to disruption of the hypogonadal-pituitary-testicular axis, consistent with mechanism of action of dietary phytoestrogen in the aromatase null mouse (Roberstson et al 2002).…”
Section: Discussionmentioning
confidence: 84%
“…The gestational exposure of rats to diethylstilbestrol decreased expression of the AR mRNA and stimulated the ESR1 mRNA in the offspring (59). Exposure of adult male rats to dietary phytoestrogens reduced fecundity, and increased ESR1 and AR mRNA in the initial segment, but decreased them in the cauda of the epididymis (60). A microarray analysis of the effects of the antiestrogen fulvestrant on gene expression in the epididymis of the bonnet monkey has demonstrated that the expression of several genes involved in fluid absorption is affected by the treatment, including a reduction in aquaporin 1 and NHE3 expression (61).…”
Section: Epididymismentioning
confidence: 96%